Impact of Visual Communication Design Study Program Curriculum Content on Consideration of Student Career Plans and Future - Kasmana, K; Annisya, N N (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
Self-competence is considered in career planning and the future of UNIKOM visual communication design study program students, at the final level. Influenced by external and internal factors, this condition encourages students to overthinking, not focusing on the impact on their college activities, a small part is disturbing to the point of requiring counseling and psychologist therapy. This article seeks to find out students’ self-understanding of future career plans, their relationship with curriculum content; the subject of the courses given in the visual communication design study program. With a qualitative approach, data were obtained through questionnaires and interviews with 106 students as case studies, structured data were analyzed descriptively. The results showed that 60% of students have good career planning skills, the careers chosen according to their core competencies include graphic designer and illustrator, photographer, videographer, content creator, visual game, animator, UI / UX Designer, and / or 3D modelling, 30% of students have the ability to plan a career as an entrepreneur, and 10% of students are still indecisive. Internal and external factors have a big influence on the understanding of interests, talents, personality, and lifestyle that support the career plan that will be pursued. In general, the curriculum content in the current study program provides freedom of choice for students to choose what they like, specific skills will be pursued through individual self-development, and educate them to be independent. The current curriculum opens up opportunities for students to be prepared for the uncertainty of careers and the future.